Gender differences in cognitive decline in centenarians and the oldest old - Bientinesi, Elisa; Monti, Daniela (The Italian Journal of Gender-Specific Medicine, 2020)
The increase in human life expectancy is a worldwide phenomenon, and the oldest old and centenarians are the segment of the elderly population that is increasing the fastest. A remarkable gender difference in life expectancy and mortality, including survival to extreme age, has been demonstrated by many studies. In a population who is getting older, dementia is one of the major age-related diseases that cause disability and dependency. Thus, the study of the oldest old and centenarians might help evaluate whether cognitive impairment is an inevitable event that occurs in ageing. Indeed, although the prevalence of cognitive impairment in centenarian studies varies widely, some of them (about 20%) preserve cognitive function and, even among those who show cognitive impairment at 100 years of age, approximately 90% delay the onset of clinically evident dementia. Moreover, considering that among the oldest old and centenarians the number of women is greater than that of men, the study of gender differences regarding the cognitive status in these subjects could help identify protective and/or non-protective biological, social and behavioral factors. This review summarizes the gender differences in cognitive impairment in the oldest old and the centenarians, focusing on some of the factors involved in the onset of dementia, such as inflammaging, apolipoprotein E (APOE) genotype, and depression.